Enhancement of 2-butanone sensing properties of SiO2@CoO core-shell structures - Vioto, Gabriel C.N. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Zito, Cecilia A. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2020)
Volatile organic compounds (VOCs) can be associated with some diseases when found in human exhaled breath as a result of alterations in metabolic pathways. Therefore, the development of highly selective sensors to a particular VOC is required. In this paper, we used silica (SiO2) nanospheres as support for the growth of cobalt (II) oxide (CoO) nanosheets, resulting in the SiO2@CoO core-shell structure with a high specific surface area. This structure was applied as a chemoresistive VOCs sensor. The SiO2@CoO material exhibited increased sensitivity to 2-butanone in comparison with acetone, methanol, ethanol, isopropanol, acetaldehyde, benzene, toluene, and m-xylene. The response to 100 ppm of 2-butanone was ~44.7, with a response time of 27 s. The enhanced performance might be attributed to the high surface area provided by the unique core-shell structure with 2D CoO nanosheets.
Keywords: Cobalt oxide; Gas sensor; Hard-template; P-type semiconductor; Selectivity; Volatile organic compounds